Introduction - Ross, Jonathan Maurice (Stridon, 2025)
This article explains the thematic focus of the current special issue, a collection of contributions that deal on macro and meso levels with the evolution of community interpreting services in the 2010s and early 2020s in what could be considered the 'European periphery', i.e., countries in Southeastern and East Central Europe. In this period, countries as varied as Turkey, Poland and Hungary were faced with massive and sudden flows of asylum-seekers and other migrants from the east, south and southeast, creating unprecedented challenges for effective communication between users and providers of public services. Due to the paucity of existing infrastructure for community interpreting, as well as the lack of interpreters with the required cultural and linguistic competen-cies, national and local governments, international organisations, NGOs, and individual interpret-ers and administrators often improvised and resorted to ad hoc remedies. The article suggests that some of the problems that arose in the field and that are addressed in the articles in the special issue (e.g., the role of the community interpreter and the status of cultural mediators) were not new and had a long-standing presence within the literature on community interpreting. It also shows how the responses of national and international bodies to the so-called refugee crisis can be conceptu-alised within the framework of humanitarian interpreting; when understanding the behaviour of individual interpreters, moreover, insights can be gained from the burgeoning field of research on non-professional interpreting.
Keywords: community interpreting; humanitarian interpreting; humanitarno tolmačenje; interpreting policy; migracije; migration; neprofesionalno tolmačenje; non-professional interpreting; skupnostno tolmačenje; tolmaška politika